Additive manufacturing of silica glass using laser stereolithography with a top-down approach and fast debinding. Issue 29 (3rd May 2018) - Liu, Chang; Qian, Bin; Liu, Xiaofeng; Tong, Limin; Qiu, Jianrong
Abstract : A new approach for glass additive manufacturing with stereolithography that raises the efficiency in a great extent. Abstract : Additive manufacturing of silica glass by stereolithography is a new technology. Improving the efficiency of this technology is an important issue. In this work, a stereolithography system using top-down approach and a compatible suspension for this approach was developed. The debinding behavior of the green part (the solidified suspension) was discussed in detail based on the results of thermogravimetric analysis and Fourier transform infrared absorption spectroscopy. A fast heat treatment within 16 hours was adopted for debinding and sintering of the green part which took only 1/3 of the time of previous report. Designed glassware which could not be processed by conventional technologies was manufactured in this way, and the products showed similar properties with fused silica, as confirmed by X-ray diffraction and UV-vis-IR spectrometer.